Microplastisphere as a crowded and inclusive micro-ecosystem in seagrass meadow: Cross-kingdom connections and microbial food web - Qiqi Wu; Yu Xia; Yiwei Tao; Chengjun Ge; Yuanyuan Zhao; Dan Feng; Hui Deng (Marine Pollution Bulletin, 2026)

Spatial heterogeneity, source apportionment and ecological risks of trace metal(loid)s in lakes across China - Xue Li; Weijie Yao; Hui Zeng; Xuan Hou; Bin Wang; Xing Yang; Chengjun Ge; Hailong Zhou; Jiwei Luo; Xueqiang Lu (Journal of Hazardous Materials, 2026)

Dark side of biodegradable microplastics in mangrove ecosystem: Plastisphere as an overlooked hotspot of sulfate-reducing metabolism - Yiqiao Zheng; Qiqi Wu; Yu Xia; Hui Deng; Yuanyuan Zhao; Jiwei Luo; Dan Feng; Chengjun Ge (Water Research, 2026)

Microplastics drive the reconfiguration of microbial sulfur cycling pathways in seagrass bed sediments - Mingguang Luo; Jinluo Fan; Xiujun Wang; Yibing Ge; Dan Feng; Shengkai Cao; Jun Wang; Hui Deng; Jiwei Luo; Yuanyuan Zhao; Chengjun Ge; Honglin Bu (Environmental Pollution, 2026)

Roadside lidar-based scene understanding toward intelligent traffic perception: A comprehensive review - Jiaxing Zhang; Chengjun Ge; Wen Xiao; Miao Tang; Jon Mills; Benjamin Coifman; Nengcheng Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Long-term natural photodegradation of plastic films enhances the molecular complexity of plastic-derived dissolved organic matter - Derong Zhang; Jiwei Luo; Xue Li; Dongming Wu; Yanhai Xie; Hui Zeng; Hui Deng; Qingmian Chen; Chengjun Ge; Ying Zhang (Water Research, 2026)

Effects of ocean acidification on intestinal homeostasis and organismal performance in a marine bivalve: From microbial shifts to physiological suppression - Minggui Liu; Xiaoyu Guo; Lanfang Han; Yuanyuan Zhao; Chengjun Ge (Marine Pollution Bulletin, 2026)

Defect-rich carbon induced built-in electric fields within molybdenum-based metal-organic framework catalysts for enhanced activity and stability in oxidative desulfurization - Juncong Zou; Yang Yan; Shanying He; Chengjun Ge; Dexin Wang; Chunping Yang (Journal of Hazardous Materials, 2026)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Distribution characteristics of black carbon in Taihu Lake sediments and their effects on microorganisms - Yan Li; Hang Su; Ke Liu; Chengjun Ge; Qingkun Wang; Xinyu Cheng; Jiang Jiang (Environmental Research, 2025)

Dissolved organic matter derived from long-term photodegradation of plastics alters microbial methane conversion in mangrove sediments - Minmin Wang; Leiqian Ma; Derong Zhang; Fan Yang; Xing Yang; Bin Wang; Xue Li; Chengjun Ge; Jiwei Luo; Ying Zhang (Bioresource Technology, 2025)

Comprehensive review on in vitro bioaccessibility of mercury in various foodstuffs - Yu Gong; Chengjun Li; Fei He; Feng Ge; Yongming Ju; Huan Zhong; Weixin Li (Journal of Hazardous Materials, 2025)

Colonization time of plastisphere drives the dynamics of organic carbon stability and microbial communities in seagrass bed sediments - Shuailing Hou; Jun Wang; Dan Feng; Dongming Wu; Shiquan Chen; Jinluo Fan; Mingguang Luo; Hui Deng; Xing Yang; Jiwei Luo; Yuanyuan Zhao; Chengjun Ge (Journal of Hazardous Materials, 2025)

Soil-aged microplastics exhibit stronger effects than air- and rainwater-aged ones on the network complexity and assembly process of soil microbial community - Faying Fu; Shu Wang; Xinran Zhang; Yu Xia; Hui Deng; Yuanyuan Zhao; Ying Zhang; Chengjun Ge (Journal of Environmental Chemical Engineering, 2025)

Lead-free perovskite Cs3Bi2Br9 quantum dots (QDs)/ultra-thin W18O49 nanobelts S-scheme heterojunction toward optimized photocatalytic CO2 reduction coupled with toluene oxidation - Mai Zhang; Xiangya Zhang; Zhen Zhang; Linlin Zhang; Jianjun Liao; Xiaodong Zhang; Chengjun Ge; Wei Zhou (Chemical Engineering Journal, 2025)

Adverse effects of microplastics on the growth, photosynthesis, and astaxanthin synthesis of Haematococcus pluvialis - Weibin Zhao; Jiaye Deng; Jiamei Wang; Chengjun Ge; Hui Yang (Science of The Total Environment, 2024)

Deciphering how endogenous mangrove litterfall influences organic matters transformation driven by microbes in sediment with exogenous microplastics inputs - Yu Xia; Shu Wang; Xinran Zhang; Faying Fu; Hui Deng; Yuanyuan Zhao; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2024)

Estimating the spatiotemporal distribution of PM2.5 concentrations in Tianjin during the Chinese Spring Festival: Impact of fireworks ban - Zhifei Liu; Kang Zheng; Shuai Bao; Yide Cui; Yirong Yuan; Chengjun Ge; Yixuan Zhang (Environmental Pollution, 2024)

Biogas slurry-derived dissolved organic matter inhibited oxytetracycline adsorption by tropical agricultural soils - Hui Chen; Lingfei Yin; Yuan He; Liangtai Bai; Yuejun Wu; Yuanyuan Zhao; Febelyn Reguyal; Ajit K. Sarmah; Xing Yang; Chengjun Ge; Hailong Wang (Science of The Total Environment, 2024)

Effects of polypropylene films and leached dissolved organic matters on bacterial community structure in mangrove sediments - Jiatong Li; Xue Li; Jiwei Luo; Peng Huang; Chengjun Ge; Xing Yang; Hailong Wang (Science of The Total Environment, 2024)

Forecasting daily PM2.5 concentrations in Wuhan with a spatial-autocorrelation-based long short-term memory model - Zhifei Liu; Chengjun Ge; Kang Zheng; Shuai Bao; Yide Cui; Yirong Yuan; Yixuan Zhang (Atmospheric Environment, 2024)

Soil total and available C:N:P stoichiometry among different parent material soil profiles in rubber plantations of Hainan Island, China - Yuzhu Li; Yue Zhao; Xuelian Bao; Hongtu Xie; Xiaotao Lü; Yangang Fu; Shixin Tang; Chengjun Ge; Chao Liang (Geoderma Regional, 2024)

Low-molecular-weight organic acids-mediated transport of neonicotinoid pesticides through saturated soil porous media: Combined effects of the molecular structures of organic acids and the chemical properties of contaminants - Bingyao Xu; Lulu Lu; Mengya Liu; Qiang Zhang; Usman Farooq; Taotao Lu; Zhichong Qi; Chengjun Ge (Chemosphere, 2024)

Identification of organic pollutants and heavy metals in natural rubber wastewater and evaluation its phytotoxicity and cytogenotoxicity - Dayu Zhu; Chengjun Ge; Ying Sun; Huamei Yu; Jun Wang; Hongfei Sun (Chemosphere, 2024)

Distribution, sources and ecological risks of per- and polyfluoroalkyl substances in overlying water and sediment from the mangrove ecosystem in Hainan Island, China - Guoliang Ren; Like Chen; Jinluo Fan; Shuailing Hou; Junnan Chen; Hui Deng; Jiwei Luo; Peng Huang; Yuanyuan Zhao; Jiatong Li; Dan Feng; Chengjun Ge; et al. (Science of The Total Environment, 2024)

Integrated microbiota and multi-omics analysis reveal the differential responses of earthworm to conventional and biodegradable microplastics in soil under biogas slurry irrigation - Yuanyuan Zhao; Huiting Jia; Hui Deng; Chengjun Ge; Wenzhe Xing; Huamei Yu; Jiatong Li (Science of The Total Environment, 2024)

Integrated microbiome and multi-omics analysis reveal the molecular mechanisms of Eisenia fetida in response to biochar-derived dissolved and particulate matters - Huiting Jia; Yuanyuan Zhao; Hui Deng; Huamei Yu; Chengjun Ge; Jiatong Li (Journal of Hazardous Materials, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Coupled anaerobic methane oxidation and metal reduction in soil under elevated CO 2 - Chenchao Xu; Naifang Zhang; Kaihang Zhang; Shuyao Li; Qing Xia; Jing Xiao; Maojun Liang; Weilei Lei; Junpan He; Gaiping Chen; Chengjun Ge; Xunhua Zheng; et al. (Global Change Biology, 2023)
Continued current emissions of carbon dioxide (CO 2 ) and methane (CH 4 ) by human activities will increase global atmospheric CO 2 and CH 4 concentrations and surface temperature significantly. Fields of paddy rice, the most important form of anthropogenic wetlands, account for about 9% of anthropogenic sources of CH 4 . Elevated atmospheric CO 2 may enhance CH 4 production in rice paddies, potentially reinforcing the increase in atmospheric CH 4 . However, what is not known is whether and how elevated CO 2 influences CH 4 consumption under anoxic soil conditions in rice paddies, as the net emission of CH 4 is a balance of methanogenesis and methanotrophy. In this study, we used a long‐term free‐air CO 2 enrichment experiment to examine the impact of elevated CO 2 on the transformation of CH 4 in a paddy rice agroecosystem. We demonstrate that elevated CO 2 substantially increased anaerobic oxidation of methane (AOM) coupled to manganese and/or iron oxides reduction in the calcareous paddy soil. We further show that elevated CO 2 may stimulate the growth and metabolism of Candidatus Methanoperedens nitroreducens , which is actively involved in catalyzing AOM when coupled to metal reduction, mainly through enhancing the availability of soil CH 4 . These findings suggest that a thorough evaluation of climate‐carbon cycle feedbacks may need to consider the coupling of methane and metal cycles in natural and agricultural wetlands under future climate change scenarios.

Mangrove degradation retarded microplastics weathering and affected metabolic activities of microplastics-associated microbes - Hui Deng; Yuqing Zhang; Dazhen Li; Qianqian Fu; Jianxiong He; Yuanyuan Zhao; Dan Feng; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2023)

Response of earthworms to microplastics in soil under biogas slurry irrigation: Toxicity comparison of conventional and biodegradable microplastics - Yuanyuan Zhao; Huiting Jia; Hui Deng; Wenzhe Xing; Dan Feng; Jiatong Li; Chengjun Ge; Huamei Yu; Ying Zhang; Haiying Chen (Science of The Total Environment, 2023)

Multiple-functionalized biochar affects rice yield and quality via regulating arsenic and lead redistribution and bacterial community structure in soils under different hydrological conditions - Xing Yang; Zhinan Dai; Chengjun Ge; Huamei Yu; Nanthi Bolan; Daniel C.W. Tsang; Hocheol Song; Deyi Hou; Sabry M. Shaheen; Hailong Wang; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Iron-modified phosphorus- and silicon-based biochars exhibited various influences on arsenic, cadmium, and lead accumulation in rice and enzyme activities in a paddy soil - Xing Yang; Ergang Wen; Chengjun Ge; Ali El-Naggar; Huamei Yu; Shengsen Wang; Eilhann E. Kwon; Hocheol Song; Sabry M. Shaheen; Hailong Wang; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Bioremediation of tetramethyl thiuram disulfide and resource utilization of natural rubber wastewater by WR-2 Bacillus-dominated microbial community - Dayu Zhu; Chengjun Ge; Hongfei Sun; Jun Wang; Liujing He (Environmental Science and Pollution Research, 2022)

Nutritional Profile and Bioremediation of Tropical Marine Aquaculture with an Integrated Microalgae and Bacteria Symbiosis - Ruiyang Ma; Shiyu Xie; Huiting Jia; Linhai Pu; Licheng Peng; Chengjun Ge (Water, Air, & Soil Pollution, 2022)

Combined Effects of Microplastics and Benzo[a]pyrene on the Marine Diatom Chaetoceros muelleri - Yuanyuan Su; Huaiyuan Qi; Yipeng Hou; Mengyi Gao; Jie Li; Minggang Cai; Xiaoshan Zhu; Miao Chen; Chengjun Ge; Dongdong Fu; Zezheng Wang; Licheng Peng (Frontiers in Marine Science, 2022)
Microplastics are regarded as ubiquitous pollutants in the ocean and have attracted worldwide concerns. Benzo[a]pyrene (B[a]P), one of typical polycyclic aromatic hydrocarbons (PAHs), is commonly detected in marine environment. Once coexisted, the microplastics and B[a]P may interact with each other and result in combined toxicity to organisms, and these remain to be systematically elucidated. Thus, this study aims to investigate (i) the effects of single micro-sized polystyrene (mPS), polyethylene terephthalate (mPET), and B[a]P on cell growth of Chaetoceros muelleri ; and (ii) the interaction of microplastics and B[a]P, and their combined effects on C. muelleri . The results showed that both single microplastics and B[a]P at a high concentration of 150 μg/L inhibited the growth of C. muelleri . For single treatment of microplastics, stronger inhibition effects on microalgae was caused by mPET than that of mPS, with the highest IR of 25.23 and 11.17%, respectively. This may be attributed to the obvious surface roughness of mPET. By comparison, the combined effects of microplastics and B[a]P significantly inhibited the growth of C. muelleri as compared with the single treatment of B[a]P ( P < 0.05). Synergistic effect was found in the combination of microplastics with B[a]P at high concentrations of 150 μg/L. Interestingly, the antagonistic effect on C. muelleri was observed in the combined treatment of microplastics and B[a]P at low concentrations of 10 μg/L. In addition, the pollutants reduced the content of photosynthetic pigments in microalgal cells. The SOD and MDA content of microalgae increased in the early stage of exposure to pollutants (e.g., Days 1 and 5), but decreased in the later stage (Day 15) compared with the control group. The decreased superoxide dismutase (SOD) and catalase (CAT) activity in single and composite systems may indicate that the antioxidative enzymatic system of microalgae has been inhibited or destroyed. This study will be helpful to further explore the ecological threats of microplastics and PAHs to the marine ecosystem.